Special education for young learners with disabilities - Obiakor, Festus E.; Bakken, Jeffrey P. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Special Education for Young Learners with Disabilities brings together leaders in the field of young children with disabilities, to present their ideas and research on different disability topics. Beginning with an introduction to the topic, the remaining chapters include discussions on learning disabilities, emotional and behavioral disorders, and intellectual disabilities; those who are deaf/hard of hearing; those who have visual impairments; those who have autism, severe and multiple disabilities, and traumatic brain injury; those who are culturally and linguistically diverse; those who have physical disabilities, and other health impairments. While this book focuses largely on the current climate of special education for young learners with disabilities, it also looks forward, concluding with a chapter on the future for the topic, both on a research and a practical basis. This volume of Advances in Special Education is a fundamental resource for special education researchers, scholars, practitioners, and professionals who teach and serve young learners with disabilities.
Prelims -- Special education for young learners with disabilities: an introduction -- Reading interventions for young learners with reading difficulties and disabilities: the role of word reading and word meaning -- The urgent and the always: intervening on behavior problems in young children -- Special education for young learners with intellectual disabilities -- Special education for young learners who are deaf/hard of hearing -- Special education for young children with visual impairments -- Special education for young learners with autism spectrum disorder -- Inclusive special education for young learners with severe and multiple disabilities -- Teaching young children with traumatic brain injury in inclusive classroom settings -- We can do better: critically reframing special education research and practice at the intersections of disability and cultural and linguistic diversity for young children -- Special education for young learners with physical disabilities -- Special education for young learners with other health impairments -- Special education for young learners with disabilities: moving forward -- Index.
Includes index.
Print version record
Keywords: Youth with disabilities -- Education -- United States; Students with disabilities -- United States -- Services for; Education -- Special Education / Physical Disabilities; Teaching of specific groups & persons with special educational needs